THE FEMININE TRADITION IN ENGLISH FICTION - O.M. Smochin (Vasyl Stefanyk Precarpathian National University, 2015)
This article on feminine tradition and linguistic approaches to gender in literature demonstrates the utility for students of gender in society at large to investigate the uses to which gender may be put in the carefully planned discourse of fiction. It reveals not what native speakers naturally do, but what they are able to understand and the inventions and models that influence their understanding.